ChemInform Abstract: Photo‐Organocatalysis of Atom‐Transfer Radical Additions to Alkenes. Issue 14 (April 2015) - Arceo, Elena; Montroni, Elisa; Melchiorre, Paolo
Abstract: The photochemical activity of a simple organic molecule enables the intermolecular atom‐transfer radical addition of haloalkanes onto olefins at ambient temperature and under illumination by a household light bulb is reported.